Nicotiana attenuata's capacity to interact with arbuscular mycorrhiza alters its competitive ability and elicits major changes in the leaf transcriptome. Issue 3 (8th January 2018) - Wang, Ming; Wilde, Julia; Baldwin, Ian T.; Groten, Karin
Abstract: To study the local and systemic effects of arbuscular mycorrhizal fungal (AMF) colonization, Nicotiana attenuata plants impaired in their interactions with AMF due to silencing of a calcium‐ and calmodulin dependent protein kinase (inverted repreat (ir) CCaMK ) were grown competitively in pairs with empty vector (EV) plants, with and without two different types of inoculum. When inoculated, EV plants strongly outperformed ir CCaMK plants. Foliar transcript profiling revealed that AMF colonization significantly changed gene expression of P‐starvation and ‐transporter genes in ir CCaMK plants. The Pht1 family phosphate transporter NaPT5 was not only specifically induced in roots after AMF colonization, but also in leaves of AMF‐colonized ir CCaMK plants, and in plants grown under low Pi conditions in the absence of AMF. The P‐starvation signature of inoculated ir CCaMK plants corresponded with increases in selected amino acids and phenolic compounds in leaves. We also found a strong AMF‐induced increase in amino acids and phenolic metabolites in roots. Plants impaired in their interactions with AMF clearly have a fitness disadvantage when competing for limited soil nutrients with a fully functional isogenic line. The additional role of the AMF‐induced Pht1 family transporter NaPT5 in leaves under P‐starvation conditions will require further experiments to fully resolve. Abstract : Plants impaired in their interactions with arbuscular mycorrhiza due to the silencing of a calcium and calmodulin dependent protein kinase (CCaMK) have a fitness disadvantage when competing for limited soil nutrients with a fully functional isogenic line and display the transcriptional signatures of P starvation in their leaves, as revealed by foliar transcriptome and metabolite analysis of competitively grown plants.